L’alternance syntaxique dans l’incise de discours direct : des normes de la grammaire aux mécanismes textuels - Raluca NITA (E-REA)
This article focuses on the syntactic variation – subject-verb, verb-subject – in the reporting clause embedded in or following a quotation, and provides a double approach of word order by combining the syntactic and the textual functioning of the reporting clause in English journalistic texts. In a general background of complex relations between reporting and reported clauses in English, punctuation and verb syntax contribute to the dependency of the verb-subject reporting clause on the reported clause and to the autonomy of the subject-verb reporting clause. At a textual level, the reference of the subject and the textual role of the speaker show that the reporting clause continues to function differently according to word order: the verb-subject reporting clause refers directly to the reported situation, whereas the subject-verb reporting clause dwells on previously introduced topics.